2006
DOI: 10.1590/s1516-89132006000700005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of static magnetic field exposure on hematological and biochemical parameters in rats

Abstract: The present work was undertaken in order to investigate the effects of static magnetic field (SMF LDH (+43%, p<0.05), AST (+ 41%, p<0.05) and ALT activities (+95%, p<0.05). In contrast, the glucose concentration was unaffected. These changes suggested that exposure to SMF had a possible effect on the proliferation of blood cells and enzymes release within blood indicating tissue alterations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…[20] Adult male Wistar rats were exposed to static magnetic field (128mT) for 1h./5 days/week for 6 weeks showed significant increase of platelet count (+10%, p<0.05) compared to control group. [21]. The immediate effects of whole body exposure to 2.450 GHz magnetic radiation on hematological parameters on 140 adult Wistar rats showed Platelet count reduced from the control value immediately after exposure then increased gradually after 1, 2, 4 and 8 weeks respectively [22].…”
Section: Discussionmentioning
confidence: 99%
“…[20] Adult male Wistar rats were exposed to static magnetic field (128mT) for 1h./5 days/week for 6 weeks showed significant increase of platelet count (+10%, p<0.05) compared to control group. [21]. The immediate effects of whole body exposure to 2.450 GHz magnetic radiation on hematological parameters on 140 adult Wistar rats showed Platelet count reduced from the control value immediately after exposure then increased gradually after 1, 2, 4 and 8 weeks respectively [22].…”
Section: Discussionmentioning
confidence: 99%
“…Regular exposure to electromagnetic field can increase plasma volume with a consequent decrease in the concentration of Hb and RBCS in blood as stated previously 16 . The decrease in the concentration of hemoglobin could be attributed to the interaction between iron of haeme and electromagnetic field, by which magnetic field enters the body and acts on ions in all the vital organs such as spleen, bone marrow, kidney and liver, it alters the cell membrane potential and distribution of ions 17 .…”
Section: Blood Picturementioning
confidence: 67%
“…It has been reported that SMF (including moderate fields) can be responsible for vascular responses in vivo. Effects can be observed in vascular and blood system components such as ion channels on the smooth muscle of the vascular wall [Gmitrov et al, ], platelet number [Amara et al, ], blood flow [McKay et al, ], and pressure [Okano and Ohkubo, ]. It is plausible that the SMF effects found here might be extended to therapeutic methods of thrombus dissolution.…”
Section: Discussionmentioning
confidence: 93%